Digital Literacy Advocacy Reflection in Movie Poster “Missing” (2023) - Diniati, Anisa; Salma, Aqida Nuril (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Posters are an advertising medium, showcasing captivating images and incorporating information and symbols to capture the audience's attention. The study aims to analyze the semiotics of the 'Missing' (2023) movie posters and explore how these semiotic meanings relate to the needs of digital literacy advocacy. The focus of the study centers on the film poster for Missing (2023), specifically analyzing one of the three official IMDb advertisements for the movie. The study uses documentary analysis techniques grounded in Ferdinand De Saussure's theory of signification to interpret the semiotics of the posters. The 'Missing' (2023) poster illustrates various aspects of digitalization through its visual elements. The poster aims to captivate viewers and pique their interest in the film. The visual elements in the illustration category, highlighting digitalization, incorporate screenshots of devices and laptops. Additionally, the poster frequently highlights the second aspect of digital literacy advocacy, highlighting the development of interconnected skills and competencies essential for the digital era.